An annotated checklist of the Niphargidae (Crustacea: Amphipoda) of Greece - Ntakis, Alexandros; Karaouzas, Ioannis; Fišer, Cene; Stoch, Fabio (Zootaxa, 2020)
Despite Greece being a global hotspot of subterranean biodiversity, its hypogean fauna is largely neglected from both an ecological and conservational point of view. An overview of the Niphargidae occurring in Greece is presented as an annotated list of all available published records. These records have resulted in an updated species list reflecting taxonomic corrections and species distribution range in the Greek peninsula. A total of 23 species, attributed to 3 genera, is up to date known from Greece with a high rate of endemicity found particularly in Crete. The endemic species of Greece amount to 21 (91% of total species richness), with the remaining species distributing also in the Republic of North Macedonia. Currently, none of them is listed in the national, European or global IUCN Red Lists of Threatened Species. Considering the increasing habitat degradation due to anthropic pressure, groundwater harvesting and climate change we could lose rare and endemic species without even acknowledging their existence.